Identity repatriation: retelling the global narrative of South West and Central Nigeria through architecture - Babalola, Toluwanimi Bamidele (My University, 2020)
Art Repatriation is a major discourse in the world today. During the periods of colonization, many art works were pillaged, looted and taken from their place of origins; consciously or unconsciously influencing the identity and narrative of those places. Africa, and subsequently Nigeria, is at the heart of this discussion of repatriation of art, with the perception of Africa moved from a place of wealth and pride to that of poverty, corruption and war. The argument here is that when these artworks were removed, the Africa’s narrative as a place of wealth was lost. HOW DO WE BRING BACK THIS NARRATIVE? The context for this exploration is Tarkwa Bay, Lagos, Nigeria. This thesis begins by highlighting how globally nations have changed their narrative and perception on the world stage through the creation of global cities such as Dubai, large scale housing developments and cultural spaces such as museums. These various approaches are being utilized as a means of indicating the social, economic and global aspirations of the nations. African nations have begun to incorporate this approach with cities such as the Eko Atlantic City, Lagos Nigeria being currently constructed .In response to the global approach of countries and how they retell their narrative, this thesis takes the approach of telling a narrative through cultural spaces (museum). It further discusses the role museums have played in telling a narrative of wealth of places. (My argument is that this is a more contextual response to telling a narrative.) The study further highlights the Bilbao Effect, a precedent for this approach whereby the construction of an iconic museum resulted in the revitalization of Bilbao, Spain. Given the success of the Guggenheim museum in Bilbao, several attempts at replicating this approach of telling a narrative and revitalizing communities have proved futile. With issues such as gentrification being the resultant effect. Taking this into consideration, gentrification is investigated to identify the positive and negative outcomes of gentrification, as well as the manner of designing for communities. With the main objective of telling a narrative of wealth, the study highlights how wealth has been classified, defined and symbolized in Nigeria over time in the form of art, architecture and various other approaches, and what the true meaning of wealth is. Furthermore, architecture and artworks depicting wealth are analysed to clearly identify underlying principles. These principles are informative in the design exploration of a museum for art repatriation in Tarkwa Bay, Lagos, Nigeria. Located just Adjacent to Eko-Atlantic city development, the objective of this museum is to create a dialogue that tells a narrative of wealth being taken (Eko Atlantic city).The museum takes into account its contextual community, as well as the environmental landscape and how the architecture becomes hybrid in nature
A research report proposal submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Masters of Architecture (Professional), 2020